Risk factors for dermatitis in submariners during a submerged patrol: an observational cohort study. Issue 6 (2nd June 2016) - Flaxman, Amy; Allen, Elizabeth; Lindemann, Claudia; Yamaguchi, Yuko; O'Shea, Matthew K; Fallowfield, Joanne L; Lindsay, Michael; Gunner, Frances; Knox, Kyle; Wyllie, David H
Abstract : Objective: The aim of this pilot study was to determine risk factors, including Staphylococcus aureus nasal carriage, for dermatitis in submariners during a submarine patrol. Participants and methods: 36 submariners undertaking a submerged 6-week patrol participated in the study. Severity of dermatitis and its impact was assessed using visual analogue scales and questionnaires at baseline and weekly throughout the patrol. S. aureus carriage levels in submariners were determined by nasal swabbing at baseline and shortly before disembarking the submarine. Occurrence of any skin or soft tissue infections (SSTI) were reported to the medical officer and swabs of the area were taken for subsequent analysis. Results: S. aureus carriers were significantly more likely than non-carriers to have previously received treatment for a cutaneous abscess (39% vs 5%, OR=13 (95% CI 1.3 to 130)) with a trend to being submariners longer (p=0.051). Skin scores at baseline and on patrol were not significantly associated with carriage status. Higher dermatitis scores were observed in those who had been submariners longer (p=0.045). Smoking and allergies were not found to be linked to carriage status or skin health score in this cohort. Conclusions: This small pilot study investigates S. aureus carriage status and skin health in submariners. Length of submarine service but not S. aureus carriage was identified as a risk factor for worsening skin health in this small cohort during a 6-week patrol. This does not support S. aureus decolonisation to improve skin health in this population. Further investigation into causes of dermatitis in submariners is required. This data supports a better understanding of the potential impact of exposure to environmental factors that could affect skin health in submariners.